Determinan pemberantasan sarang nyamuk pada ibu rumah tangga di Bogor - Mayumi Nitami; Sri Tjahyani Budiutami (Berita Kedokteran Masyarakat (BKM), 2016)
Determinants of dengue mosquito eradication (PSN) in the households in Bogor in 2016PurposeThis study aimed to determine the factors that affect of PSN on housewives in Cibinong and the factors found that influence were: job, knowledge, attitude, behavior of housewife, counselling, active jumantik, giving abatement and the number of container.MethodsA cross-sectional study was conducted using 125 housewifes in Cibinong sub-district. The statistical analysis used chi-square and multiple logistic regression tests.ResultsThis study showed that counseling and the existence of jumantik cadre were the determinants of the application of mosquito nest eradication. Counseling was the most influential factor on the application of mosquito nest eradication.Conclusion Dengue control and prevention counseling should be given to all age groups in the community regularly and it is recommended to reactivate jumantik cadres.